Hydration status, knowledge, and behavior in youths at summer sports camps - Decher, N. R.; Casa, D. J.; Yeargin, S. W.; Ganio, M. S.; Levreault, M. L.; Dann, C. L.; James, C. T.; McCaffrey, M. A.; O`Connor, C. B.; Brown, S. W. (International Journal of Sports Physiology and Performance, 2008)
Purpose: To assess the hydration status and level of hydration knowledge of youths at summer sports camps. Methods: Sixty-seven active youths, 57 males (mean ± SD, 12 ± 2 y, 136 ± 16 cm, 50.6 ± 21.1 kg) and 10 females (13 ± 2 y, 153 ± 8 cm, 45.2 ± 9.0 kg) participated in 4 d of sports camp. Hydration status was assessed before the first practice (AM) and after the second practice (PM). Participants completed surveys assessing hydration knowledge (HAQ) and hydration habits on day 3 and a selfassessment (EQ#1). Results: Mean AM urine specific gravity (USG) and urine osmolality (Uosm) scores ranged from minimal to significant dehydration across 4 d, even when temperatures were mild. Correlations between hydration indices and EQ#1, ranging from 0.11 to -0.51, were statistically significant (P < .05), indicating that subjects recognized when they were doing a good or bad job hydrating. HAQ did not correlate strongly with hydration indices suggesting other impediments to hydration. Thirst correlated negatively with EQ#1 (from -0.29 to -0.60). Conclusion: Hydration at summer sports camp is a concern and special efforts need to be made to help youths develop hydration strategies.